Vozes da escrita feminina no Brasil: da função social ao poder humanizador da poesia - Martins, Simone Maria (2019)
This thesis presents a bibliographical research through comparative studies, which draws and interlates four voices of Brazilian literature in the field of female writing, through the analysis of three categories: poetry - woman - education. In the thesis, we sought to highlight the fact that women reached a larger space in society through writing, starting from the Nisia Floresta, which describes a very different reality today, where it fought against women's civil, political and social rights. Tracing the studies of Nísia Floresta as a starting point, we intend to emphasize their importance in the struggle for the emancipation of women, who used writing as the main source of protest against a segregated and chauvinistic society that did not allow women to take part in public life. In continuity with the thinking and poetic expressions of Nísia Floresta, this study seeks a comparative analysis in the voices of Cecília Meireles, Helena Kolody and Adélia Prado, women who mark feminine poetic writing for the emancipation and social freedom of women. For this reason, the proposal weaves the course of each poet, pointing out what unites them in the three categories of analysis. he methodological basis of this work proposes a comparative bibliographical study and historical-literary analysis. For the compared study it is sought as theoretical and methodological support Clements (1978), Eduardo Coutinho and Tania Franco Carvalhal (1994); jointly in the critical analysis and the humanizing function of literature in Antonio Candido (2006). In addition, a reflection is provided through concepts and definitions of authors who sought to highlight the power of poetry, listed in this study as main references: Aristotle (1992), Camoes (1984), Hegel (1980), Nietzsche (1995) and Kant (1996). In the final considerations, the contributions of each of these voices that are so striking in Brazilian literature are outlined, outlining the extreme importance of poetic writing and its humanizing function, something so essential for the development of a less prejudiced and intolerant society, current days.